Imageshack - 32201349.png

Help, please .

I have the answer which is :

dz = (2xe–xy – x2ye–xy)dx – x3e–xydy =xe–xy((2 – xy)dx – x2dy).Can you show me what step exactly do we take in order to get there. Thx

Printable View

- Mar 7th 2011, 06:19 PMTronTotal differential
Imageshack - 32201349.png

Help, please .

I have the answer which is :

dz = (2xe–xy – x2ye–xy)dx – x3e–xydy =**xe****–xy****((2 – xy)dx – x****2****dy).**Can you show me what step exactly do we take in order to get there. Thx - Mar 7th 2011, 06:37 PMtopsquark